Violation of the Constitutional Rights of the Ahmadiyah Manis Lor Congregation in the Perspective of Freedom of Religion - Jaedin - Jaedin; Rahayu Rahayu; Yunanto Yunanto (Jurnal Ilmiah Dunia Hukum, 2025)
This study examines violations of the constitutional rights of the Indonesian Ahmadiyya Congregation (JAI) in Manis Lor, Kuningan, particularly in terms of administrative aspects of marriage and freedom of religion. The main issues are restrictions on religious activities and obstacles to marriage registration, which result in discrimination against the basic rights of the congregation. These violations range from restrictions on activities, intolerance in the form of rejection by civil society, and human rights violations in the form of government intervention. The research used a normative legal method with a legislative and conceptual approach, looking at empirical facts in the field, as well as John Rawls' analysis of justice as fairness to assess the principles of equality and legal justice. The results of the study show that regional policies such as Kuningan Regent Decree No. 451.7/KEP.58-Pem. Um/2004 and Circular Letter No. 300/477-Kesbangpol/2005, and West Java Governor Regulation No. 12 of 201, Letter No. 200.1.4.3/4697/BKBP and Letter No. 200.1.4.3/4666/ BKBP prohibiting and restricting Ahmadiyah activities that contradict Article 27 paragraph (1), Article 28D paragraph (1), Article 28E paragraphs (1)-(2), and Article 29 paragraph (2) of the 1945 Constitution, which guarantee freedom of religion and equality before the law. Therefore, the Supreme Court and the Administrative Court (PTUN) as judicial institutions under its authority must revoke and annul the regulation. The study recommends the revocation of this discriminatory policy and the harmonization of local regulations with the 1945 Constitution and Law No. 39 of 1999 on Human Rights, so that the principles of constitutional justice and freedom of religion can be realized in Kuningan Regency